Assistive products for long-term care among older people with chronic obstructive pulmonary disease in Japan: a retrospective cohort study - Satomi Kitamura; Rumiko Tsuchiya-Ito; Reina Taguchi; Tomoki Ishikawa; Tomoyuki Ota; Shota Hamada (BMC Geriatrics)
Abstract Background Assistive products support energy conservation in older adults with chronic obstructive pulmonary disease (COPD) that exhibits some disease-specific symptoms, such as dyspnea. This study aimed to determine the utilization of assistive products under long-term care (LTC) insurance and evaluate its association with COPD. Methods We conducted a retrospective cohort study using anonymized medical and LTC insurance claims data obtained from a Japanese city. The participants were ≥ 65 years old and first certified as requiring LTC between April 2015 and March 2020. We selected seven assistive products, that could support the daily activities of older adults with COPD with utilization rates of 1.0% or more: handrails/grab bars, ramps, canes, walkers, wheelchairs, electronic beds, and bathing aids. After stratifying care needs levels into care needs level 1 or lower and care needs level 2 or higher, we conducted multivariable logistic regression analyses to evaluate the association between the presence or absence of COPD and the use of each assistive product during the six months following certification, adjusting for sociodemographic and physical characteristics. Results Among 18,597 participants, 769 (4.1%) had COPD. The assistive products frequently used by participants with COPD included handrails/grab bars (10.9%) and bathing aids (5.2%) among those requiring low care levels, and electronic beds (36.8%), handrails/grab bars (25.4%), and wheelchairs (15.3%) among those requiring middle to high care levels. Among participants requiring low care levels (n = 13,773), those with COPD were less likely to use handrails/grab bars (adjusted odds ratio [AOR], 0.72; 95% confidence interval [CI], 0.54–0.95) and more likely to use bathing aids (AOR, 1.51; 95% CI, 1.01–2.25) compared with those without COPD. Among participants requiring middle to high care levels (n = 4,824), none of the assistive products had a significant association with COPD. Conclusions Older adults with COPD requiring low care levels were more likely to use assistive products for bathing than those without COPD, but the use of handrails/grab bars was less in those with COPD than that of those without. These results could be helpful to healthcare providers and policymakers when considering assistive product use for LTC to manage respiratory symptoms.